LUKISAN KACA NAGASEPAHA, BULELENG -BALI - Eddy Hadi Waluyo (Jurnal Dimensi Seni Rupa dan Desain, 2006)
AbstractGlass painting is a kind of painting that is being drawn and painted from the back side of a glass plain, and it is done in a reverse way. The painters that did not have ample formal education, prefer to use glass as their material, because of the low price, and the result is much more fascinating. Glass painting is regarded as a folk art, for it is indeed made by ordinary people who want to express their religious affirmations, feelings, hopes and their aspirations, or even their disappointment and fears. Along with its growth, glass painting has had many kinds of development. Quality wise, many of them are inclining, but some are showing to decline. Glass painting found in Bali, shows various social constructs with its dynamics and development, either individually or socially.AbstrakLukisan kaca adalah jenis lukisan yang digambari dan diwarnai dari sisi belakang bidang kaca, clan ciikerjakan dalam keadaan terbalik. Para pelukis yang pada umumnya tidak memiliki pendidikan formal yang tinggi, memilih bahan kaca karena harganya yang murah dikategorikan dalam folk art karena memang lahir dari masyarakat kebanyakan yang ingin mengungkapkan rasa religiusitasnya, perasaan-perasaannya, harapan dan aspirasinya, atau juga kekecewaan dan kecemasannya. Dalam perjalanannya, seni lukis kaca telah melalui berbagai perkembangan, balk yang bersifat inklinatif maupun deklinatif. Lukisan kaca Bali, Buleleng-Nagasepaha mencerminkan berbagai konstruk sosial dengan dinamika clan perkembangannya, baik secara individual maupun kemasyarakatan.